Lung abscess with pneumonia after SARS-CoV-2 infection – a case report - Borys, Renata; Szeliga, Ewa; Wojtuń, Kazimierz; Kużdżał, Adrian; Sawka, Karolina (Publishing Office of the University of Rzeszow, 2024)
Introduction and aim. Some patients after the SARS-CoV-2 infection may be at higher risk of consequent bacterial or fungal infections even if they have no risk factors (advanced age, obesity, metabolic diseases). A possible complication of SARS-CoV-2 infection is lung abscess with pneumonia what requires further examination and specialized treatment as well as the pulmonary rehabilitation. Description of the case. This report presents all stages of the diagnosis and treatment of lung abscess with pneumonia of male patient, aged 42 years in course of COVID-19. The article emphasizes the role of pulmonary rehabilitation in decreasing the number of postoperative pulmonary complications. Presented case report includes a description of a rehabilitation program conducted during the patient’s hospitalization. Conclusion. Lung abscess is a serious disease with an often unpredictable course, complications and an uncertain prognosis. However, most patients can be treated conservatively, and the priority in treatment is antibiotic therapy and physiotherapy treatments.
The study was conducted according to the guidelines of the Declaration of Helsinki, and approved by the Ethics Committee (protocol code No. 10/01/2021). The patient gave his written consent to the publication of his case report.
Keywords: brain fog; COVID-19; lung abscess; respiratory failure; SARS-CoV-2